Peningkatan Hasil Belajar dengan Model Problem-Based Learning di Kelas V Sekolah Dasar Negeri Kota Padang - Zakiah Mutmainnah; Yarisda Ningsih (Universitas Negeri Padang, 2023)
This research intended to assess the improvement of scale and floor plan learning outcomes using a Problem-Based Learning model (PBL) in Class V of SDN 12 Padang Besi Kota Padang. This research is a classroom action research (PTK) with 2 learning cycles. The subjects of the study were teachers and 24 students. Data analysis is carried out by qualitative and quantitative methods. The instruments used are RPP assessment sheets, observation sheets for teachers and students, test sheets in the form of questions and non-test sheets. Research result data: 1) The average score of the first cycle of RPP I 84.72% increased to 94.44% in the second cycle, 2) the average score of the first cycle of teacher implementation 85.71% increased to 96.42% in the second cycle, 3) the average value of the implementation of the first cycle of students from 85,71% to 92.85% in the second cycle, d) the learning outcomes of the first cycle of 84,02 increased to 90,02 in cycle II. The results of the study proved that using a Problem-Based Learning model (PBL) can improve learning outcomes on a scale and floor plan in Class V SDN 12 Padang Besi Kota Padang.